Fluorescent Pseudomonad Association in Plant Rhizosphere - Intan Febriani; Linda Advinda; Dezi Handayani; Siska Alicia Farma; Dwi Hilda Putri (Jurnal Serambi Biologi, 2023)
Plant growth promoting rhizobacteria or known as Plant Growth Promoting Rhizobacteria (PGPR) are bacteria found on the surface of plant roots and are beneficial microorganisms. The rhizosphere is an ideal area for the growth and development of soil microorganisms. This situation is supported by its function, namely as a provider of nutrients and also as a place for the growth and development of microorganisms. One of the bacteria found in the rhizosphere of plants is the fluorescent pseudomonad. Fluorescent pseudomonads are biological agents that can be isolated from the surface area of plant roots. This study aims to collect and analyze articles related to the association of fluorescent pseudomonads from plant rhizosphere. This type of research is research that uses the literature review method and literature collection using internet sources from the Google Scholar database. This stage consists of identification, screening, eligibility and acceptance. Based on the articles collected, it was found that the use of fluorescent pseudomonads as a biological control agent has been widely carried out because of their ability to produce antimicrobial compounds.